2006
DOI: 10.1177/0894845305283004
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Career Decision-Making Self-Efficacy, Vocational Identity, and Career Exploration Behavior in African American High School Students

Abstract: This study explores the relationship between the social cognitive construct of career decision-making self-efficacy and the outcome variables of vocational identity and career exploration behaviors in a sample of 72 urban African American high school students. The results indicate that higher levels of career decision-making self-efficacy are related to both a more differentiated vocational self-concept and to greater engagement with career exploration activities. Implications for career guidance and future re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
0
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 17 publications
(27 reference statements)
11
93
0
16
Order By: Relevance
“…The power of future orientation to influence adolescent behavior is based on expectancy-value theory, which posits that individuals modify current behavior based on their judgment of future outcomes (7) and specifically: (1) how much one values an outcome and (2) the likelihood of the outcome occurring. Research has linked greater future orientation with improved health and educational outcomes such as reduced drug use, less sexual risk taking behaviors, lower violence involvement, and improved educational and vocational outcomes (3,4,8,9). For example, Borowsky and colleagues (2009) (8) (8) (8) used a nationally representative longitudinal sample and found perceived early fatality was related to police arrest (OR 1.26; p<.05) and an HIV diagnosis (OR 7.13; p<.001) 5 years later.…”
Section: Definition Of Future Orientationmentioning
confidence: 99%
“…The power of future orientation to influence adolescent behavior is based on expectancy-value theory, which posits that individuals modify current behavior based on their judgment of future outcomes (7) and specifically: (1) how much one values an outcome and (2) the likelihood of the outcome occurring. Research has linked greater future orientation with improved health and educational outcomes such as reduced drug use, less sexual risk taking behaviors, lower violence involvement, and improved educational and vocational outcomes (3,4,8,9). For example, Borowsky and colleagues (2009) (8) (8) (8) used a nationally representative longitudinal sample and found perceived early fatality was related to police arrest (OR 1.26; p<.05) and an HIV diagnosis (OR 7.13; p<.001) 5 years later.…”
Section: Definition Of Future Orientationmentioning
confidence: 99%
“…By contrast, adolescents with a high degree of coherence and differentiation of identity show decisional capacity, and appropriate educational and social behaviours. In particular, subjects with a status of Achievement manifest a high level of decisional self-effectiveness and differentiation of interests, and those in Moratorium and Foreclosure status show a low level of selfeffectiveness in choices and diversification of professional preferences (Gushue, Scanlan, Pantzer, & Clarke, 2006;Nauta & Kahn, 2007). In the identity diffusion stage, students are unmotivated to even begin the exploration process.…”
Section: Introductionmentioning
confidence: 98%
“…Research on this concept has suggested that vocational identity is linked to clear and stable career goals, interests, personality and talents (Holland, Daiger, & Power, 1980), job satisfaction (Carson & Mowsesian, 1993;Holland & Gottfredson, 1994), career exploratory behaviors (Gushue et al, 2006), and college major choice (Leung, 1998). Although participants in this study may have not fully reached a sense of complete vocational identity, the purpose of the study was to examine its development.…”
Section: Vocational Identity: What Is It?mentioning
confidence: 99%